2020
DOI: 10.3389/fbioe.2020.556110
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Analysis of VenaTech Convertible Vena Cava Filter Using Computational Fluid Dynamics

Abstract: The VenaTech convertible filter (VTCF) has been widely used as an inferior vena cava (IVC) filter to prevent fatal pulmonary embolism in patients. However, its hemodynamics that greatly affect the filter efficacy and IVC patency are still unclear. This paper uses computational fluid dynamics with the Carreau model to simulate the non-Newtonian blood flows around the VTCF respectively deployed in the normal, reverse and three converted states in an IVC model. The results show that the prothrombotic stagnation z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Due to the continuity of blood flow, the low-speed zones around filter wires creates an acceleration effect inside the cone and between any two wires, as shown in Figures 8B,C . Wang et al (2020) called this acceleration mechanism the “viscous block”.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the continuity of blood flow, the low-speed zones around filter wires creates an acceleration effect inside the cone and between any two wires, as shown in Figures 8B,C . Wang et al (2020) called this acceleration mechanism the “viscous block”.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that there is the obvious stagnant and recirculating flow downstream of the filter head, which possibly traps emboli for potential thrombogenesis. The simulation data of VenaTech convertible filter (B. Braun, Melsungen, Germany) by Wang et al (2020) also showed the stagnation and recirculation zone downstream the filter head. At present, there are remarkable differences in the structure pattern of filter head between different IVCFs used in clinic.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations